Penggunaan Jalur dalam Multipath Routing secara Proporsional Berdasarkan Kebutuhan Bandwidth Pengguna pada Software Defined Networking - Muhamad Miftahur Ridhoilah; Achmad Basuki; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Multipath routing is a routing method that uses more than one path for transferring data in Network. Using multipath routing can cause not proportional traffic distribution. In a network with different bandwidth, evenly distributed traffic can cause a drop in data transfer performance because of the bottleneck in one of the available paths. This paper proposes a system that controls traffic distribution according to the value of demand (traffic from the user) and path unused bandwidth. The system uses Sflow-rt to monitor the value of demand and path unused bandwidth and uses group action feature of Openvswitch to distribute the traffic. The values from Sflow will be used to calculate the weight of all available paths that control traffic distribution. The test result shows traffic distribution that considers the value of demand and prioritizes path with more unused bandwidth. The system response time that change traffic distribution is effected by the value of Sflow polling. If the value of Sflow polling is 1, then system response time is in range of 1 to 3 seconds. If the value of Sflow polling is 3, then system response time is in range of 1 to 5 seconds. If the value of Sflow polling is 10, then system response time is in range of 14 to 16 seconds with a chance of no change in traffic distribution.